Painel 2 - Controle dos atos de concentração em um contexto global / Merger review in a global context . - Oliveira, Gesner; Reynolds, Michael; Bruna, Sérgio; Fagundes, Jorge; Vasconcellos, Luís Fernando; Matos , César (Revista do IBRAC, 2025)
Chairman Gesner de Oliveira Michael Reynolds – Allen & Overy Luis Fernando Rigato Vasconcellos – Secretário Adjunto da SEAE Jorge Fagundes – Economista Sergio Varella Bruna – Advogado